Intimate relationship and subjectivity in the fictions of Shang Wanyun, Li Yijun and Li Zishu - Tan, Soo Geok (2019)
For traditional love and marriage relationship, man is normally an independent and comprehensive entity, likewise woman is normally at the position as a dependent or as “the other”. Since 1970s, Mahua female writers have been thinking of the woman’s predicament and self-consciousness issues. They have some writings in relations to the topic which have demonstrated their concern over women. Shang Wan Yun, Lee Yi Jun and Li Zi Shu, who were active writers during the periods of 1970-80s, 1980-90s and 1990s till now respectively, in producing quite a number of such fictions. They have profound and wide-angle thoughts on the issues of love, marriage, family and sex. The descriptions on women’s autonomy in love and marriage relationship in their fictions are more prominent. Their fictions are reflecting the social phenomena and life aspect in Malaysia, as well as the changes in life. The main focus of this thesis is not on the descriptions of story in the love and marriage relationship, instead the main focus is on the exploration of the contents of their fictions on Malaysian women’s predicaments and experience in love and marriage relationship since 1970s, as well as women’s consciousness on self-autonomy. The study contents of this thesis consist of the writers’ perceptions on women’s self-autonomy for matrimony and their own body. So far in academic field, there is neither study nor forum to place these three writers under the same platform on the topics of love and marriage relationship and women’s autonomy. The conclusion of this study is that the fiction of the three writers reveal that patriarchal ideology has firmly dominated the fate of women, which makes women lose their subjectivity and liberty in marriage, love, sex, fertility, and self-development.